2009
DOI: 10.1007/s11665-008-9259-8
|View full text |Cite
|
Sign up to set email alerts
|

Processing Effects on Grain Refinement of AZ31 Magnesium Alloy Treated with a Commercial Al-10Sr Master Alloy

Abstract: The effects of Sr amount and melt holding time on the grain refinement of AZ31 magnesium alloy treated with a commercial Al-10Sr master alloy are investigated. The effects of solutionizing, rolling, and remelting of commercial Al-10Sr master alloy on the grain refinement of AZ31 magnesium alloy are also investigated. An increase in Sr amount from 0.01 to 0.1 wt.% or melt holding time from 20 to 80 min causes the grain size of AZ31 alloy treated with the commercial Al-10Sr master alloy to gradually decrease. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…All the bioimplant failed under the combined effect of both mechanical and corrosion properties. Severe plastic deformation [42], shot peening [43], laser treatment [44], and Mg [49] Casting and alloying (Ca) 130 --30 AZ91 [50] Casting and extrusion 80 5 AZ31 [51] Casting and alloying (Sr) 200 68 AZ31 [42] Casting and ECAP 100 2 Mg-Ca-Zn [52] Casting, extrusion and ECAP 130 2 0.7 -Mg-Zn-Ca [28] Casting and ECAP 220 -20-30 burnishing are some of the processes where mechanical properties such as tensile strength and fatigue strength can be improved. The manufacturing process [45] and alloying [20] also influence the change in mechanical and corrosion properties by altering the grain size as shown in Table 5.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…All the bioimplant failed under the combined effect of both mechanical and corrosion properties. Severe plastic deformation [42], shot peening [43], laser treatment [44], and Mg [49] Casting and alloying (Ca) 130 --30 AZ91 [50] Casting and extrusion 80 5 AZ31 [51] Casting and alloying (Sr) 200 68 AZ31 [42] Casting and ECAP 100 2 Mg-Ca-Zn [52] Casting, extrusion and ECAP 130 2 0.7 -Mg-Zn-Ca [28] Casting and ECAP 220 -20-30 burnishing are some of the processes where mechanical properties such as tensile strength and fatigue strength can be improved. The manufacturing process [45] and alloying [20] also influence the change in mechanical and corrosion properties by altering the grain size as shown in Table 5.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…It has been reported that adding minor Sr to AZ31 alloy can effectively reduce the grain size of the alloy and thus enhance its mechanical properties such as yield strength (YS), ultimate tensile strength (UTS) and elongation. [1][2][3][4] However, the reasons for such effects of Sr addition are not well understood. The present work will focus on the effects of Sr addition on the precipitates of AZ31 magnesium alloys and which may tell us the reason why Sr addition can refine the grain size and enhance the mechanical properties of the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations are mostly focused on the grain refinement of the alloys. It has been reported that adding minor Sr to AZ31 alloy can effectively reduce the grain size of the alloy and thus enhance its mechanical properties such as yield strength (YS), ultimate tensile strength (UTS) and elongation 14. However, the reasons for such effects of Sr addition are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Among the wide range of magnesium alloys, aluminum bearing magnesium alloys (Mg-Al alloys) have a dominating role in components production [4][5][6]. The broad range of applications of Mg-Al alloys depends on their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%